Sertoli–Leydig cell tumors: current status of surgical management: literature review and proposal of treatment. (May 2013) - Litta, Pietro; Saccardi, Carlo; Conte, Lorena; Codroma, Anna; Angioni, Stefano; Mioni, Roberto
Abstract To identify the appropriate management we review the current literature on the diagnostic and different surgical procedures to which the patients affected by Sertoli–Leyding cell tumors (SLCTs) were submitted. Through the description of a case report we also propose an interdisciplinary diagnostic approach and a laparoscopic surgical staging, with a long-term follow-up. The analysis shows that pelvic ultrasound is primary diagnostic procedure, and only 36% of publications clearly describe to have performed more specific investigation. The hormone assessment is performed in the presence of specific endocrine symptoms. Laparoscopic approach is chosen by a few surgeon. Laparotomic surgery is preferred based in not recent recommendations for ovarian cancer treatment, although it is demonstrated the efficacy and safety of laparoscopy in the treatment of ovarian epithelial tumors. Different steps that are usually used for oncological ovarian cancer staging are not always performed. Conservative and fertility sparing surgery is commonly accepted, and even preferred due to the young age of patients. In the surgical treatment of SLCTs is necessary to adopt common guidelines, and evenly define the steps that the patient should be submitted. If are observed epithelial cancer oncological principles, laparoscopic surgery should be the approach of choice for these patients.